2019
DOI: 10.1007/s00033-019-1143-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cross-diffusion on the stability of a triple-diffusive Oldroyd-B fluid layer

Abstract: The onset and stability of a triple cross-diffusive viscoelastic fluid layer is investigated. The rheology of viscoelastic fluid is approximated by the nonlinear Oldroyd-B constitutive equation which encompasses Maxwell and Newtonian fluid models as special cases. By performing the linear instability analysis, analytical expression for the occurrence of stationary and oscillatory convection is obtained. The numerical results show that the elasticity and cross-diffusion effects reinforce together in displaying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
(36 reference statements)
0
17
0
Order By: Relevance
“…Gentile and Straughan [22] studied tridispersive thermal convection in a porous medium of which one of the diffusive components is temperature. Raghunath et al [23] investigated the problem of triple diffusive convection in an Oldroyd-B fluid with cross-diffusion. They found that viscoelastic parameters influence the stability of the stationary bifurcation.…”
Section: Introductionmentioning
confidence: 99%
“…Gentile and Straughan [22] studied tridispersive thermal convection in a porous medium of which one of the diffusive components is temperature. Raghunath et al [23] investigated the problem of triple diffusive convection in an Oldroyd-B fluid with cross-diffusion. They found that viscoelastic parameters influence the stability of the stationary bifurcation.…”
Section: Introductionmentioning
confidence: 99%
“…The critical value of RTo with respect to the wave number, denoted by RTco, is calculated using the procedure explained by Raghunatha et al. [21].…”
Section: Linear Instability Analysismentioning
confidence: 99%
“…Recently, Raghunatha et al. [21] explored the ramifications of cross diffusion terms on the onset of triple‐diffusive convection in an Oldroyd‐B fluid layer and uncovered some of the unfamiliar results not noticed in double diffusive viscoelastic fluid systems.…”
Section: Introductionmentioning
confidence: 99%
“…It is intriguing to note that the existence of cross‐diffusion in the diffusivity matrix contributes significantly to the instability of the system and even alters the character of the instability mechanism. The intricacies of cross‐diffusion on convective instability in a triply diffusive Newtonian fluid layer have been deliberated by Terrones 44 and in an Oldroyd‐B fluid layer by Raghunatha et al 45 Nonetheless, off‐diagonal contributions on the onset of triple‐diffusive convection in a porous layer have not been explored despite recognizing the ramifications of cross‐diffusion terms on the instability characteristics. We have examined the effect of all nine elements in the diffusivity matrix on the instability of the viscoelastic triply diffusive fluid‐saturated porous layer for the first time in this article.…”
Section: Introductionmentioning
confidence: 99%